2023
DOI: 10.3390/infrastructures8050084
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Multi-Recyclability of Recycled Plastic-Modified Asphalt Mixtures

Abstract: Although the benefits of asphalt recycling have been scientifically proven and several best practices are being implemented, further research is required in specific and specialized areas. One of these circumstances is the recycling of Reclaimed Asphalt Pavements (RAPs) that contain asphalt modifiers such as elastomers and/or plastomers. Following the principles of the circular economy and considering the sustainability implications of asphalt mixtures, this paper deals with the multi-recyclability of asphalt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In this study, a Bruker Tensor 27 FTIR with an attenuated total reflectance (ATR) diamond crystal was employed to analyse the changes in the chemical functional group of the aged binders. This technique identifies chemical functionalities corresponding to distinct bonds or functional groups as a function of wavenumber by determining the infrared light absorbed by the bonds in molecules when its frequency matches the vibration frequency of the bonds [3]. The literatures showed that the spectral peaks corresponding to the wavelengths around 1030 cm −1 (sulfoxide group) and around 1700 cm −1 (carbonyl group) are significantly affected during the ageing process.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a Bruker Tensor 27 FTIR with an attenuated total reflectance (ATR) diamond crystal was employed to analyse the changes in the chemical functional group of the aged binders. This technique identifies chemical functionalities corresponding to distinct bonds or functional groups as a function of wavenumber by determining the infrared light absorbed by the bonds in molecules when its frequency matches the vibration frequency of the bonds [3]. The literatures showed that the spectral peaks corresponding to the wavelengths around 1030 cm −1 (sulfoxide group) and around 1700 cm −1 (carbonyl group) are significantly affected during the ageing process.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…The G indicates the lost deformation energy of the material and serves as the viscous component of the material, whereas the G represents the energy stored in the system and reflects the elastic part of the material. The parameter G is directly proportional to the loss factor that often depicts material losses, and which indicates the softness or hardness of the asphalt binder [3]. Since G -G equilibrium indicates the structure of a material, a rheological investigation employing this approach is regarded as valid for evaluating the behaviour of the ageing of asphalt binders.…”
Section: Temperature Sweep Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycled materials of different origins, such as construction and demolition waste [7][8][9][10][11][12][13], plastics [14][15][16][17][18][19][20], rubber [21][22][23][24][25][26], reclaimed asphalt [10,19,24,25,[27][28][29][30][31][32][33][34][35][36][37], and mineral sludge [38][39][40][41][42][43][44], have the potential for recycling in road pavement materials, making the performance of the corresponding mixtures in which they are employed comparable to those obtained with totally virgin components.…”
Section: Introductionmentioning
confidence: 99%